Manajemen Laboraturium Komputer Jurusan TKJ Di SMK Swasta PAB 8 Sampali - Yuni Syafriani (Student Research Journal, 2024)
The research entitled "Computer Laboratory Management TKJ Department at PAB 8 Sampali Private Vocational School" aims to produce and increase the efficiency of computer laboratory management in schools. This research is to fulfill the need for a comprehensive evaluation of the laboratory management system, identify existing problems, and find solutions to improve performance and effective use of laboratory facilities. The method used is a qualitative descriptive method with a case study approach. Data collection was carried out through direct observation, interviews with the school head, head of infrastructure, head of curriculum, head of laboratories and teachers, as well as analysis of documents related to the PAB 8 Sampali Private Vocational School. The research results show that the management of the computer laboratory at the PAB 8 Sampali Private Vocational School still faces several challenges, such as unscheduled hardware maintenance, limited access to the latest software, and budget planning that is not always adequate. However, the school has implemented several strategies, such as a regular maintenance schedule and collaboration with external parties for technology updates. Based on these findings, recommendations are provided to improve computer laboratory management. It is hoped that the implications of this research can make a positive contribution to curriculum development and resource management at PAB 8 Sampali Private Vocational School.